The olive biophenol hydroxytyrosol in neutral aqueous solutions – a UPLC-MS/MS investigation of its stability and oxidative color formation - Wong, Yue Ling; Boulos, Samy; Nyström, Laura (Frontiers in Nutrition, 2025)
Olive pomace is a by-product of the olive oil industry rich in biophenols such as hydroxytyrosol, with potential to be valorized as a functional ingredient. To investigate the stability of hydroxytyrosol in neutral aqueous solutions, the oxidative transformation of 50 ppm hydroxytyrosol in real and simulated tap waters over 5 days was studied with UV/Vis spectroscopy and UPLC–MS/MS. Simulated tap water systems consisted of 241 mg/L NaHCO3, with or without 139 mg/L CaCl2, and a pH range of 6.5–8.0. Hydroxytyrosol in real tap water was completely transformed to various oxidation products after 1 day, exhibiting a marked red color (λmax = 490 nm). Similarly, the simulated tap water system with a chemical composition closest to that of real tap water was largely able to reproduce this behavior with 85% hydroxytyrosol oxidation. A number of hydroxytyrosol oxidation products were annotated, including the red chromophore 2-(2-hydroxyethyl)-5-hydroxy-benzoquinone, which was formed through hydroxytyrosol autoxidation in the presence of bicarbonate ions. The chromophore’s formation without addition of transition metals, enzymes or H2O2 is presented for the first time. The results have implications for the stability and color behavior of olive pomace-derived biophenols applied to neutral or mildly alkaline environments.